Natural Infection of Covert Mortality Nodavirus in Small Yellow Croaker in Coastal Water - Xu, Tingting; Li, Yingxia; Shan, Xiujuan; Hao, Jingwei; Wu, Qiang; Tang, Kathy F. J.; Zhang, Qingli; Yao, Cuiluan (Frontiers in Marine Science, 2021)
Covert mortality nodavirus (CMNV) is an alphanodavirus mainly infecting marine shrimp and co-inhabiting organisms in aquaculture ponds. To evaluate the possibility of CMNV prevalence in the wild fish species, epidemiological survey of CMNV infection in Larimichthys polyactis, the dominant species in the Yellow Sea and East China Sea, were conducted in present study. We performed CMNV RT-LAMP assay in samples of L. polyactis collected in August 2018 and 2019 and found that CMNV prevalence was 18% and 7%, respectively. The nucleotide sequences of both RdRp and capsid protein genes of CMNV from L. polyactis were 99% similar to those of CMNV isolated from shrimp. CMNV-positive L. polyactis exhibited necrosis of cardiac muscle, oocytes loosely arranging, severe cytoplasmic vacuolation of hepatocytes, moderate pyknosis of brain pyramidal cells, degenerate renal tubular cells with ill-defined margins, and declined spleen cells in the histological examination. Moreover, CMNV positive signals were further observed in pyramidal cells of the brain, the cortical area of the kidney, oocyte growth rings, and in necrotic tissues of cardiac muscle, liver, and spleen in the in situ hybridization assay. The results revealed that CMNV had colonized in the wild populations of L. polyactis and the ecological risk of CMNV spread and epidemic in wild fish in the coastal water was un-negligible.